Pengaturan Tindak Pidana Kejahatan Perang Di Indonesia: Politik Hukum Undang-Undang Nomor 26 Tahun 2000 Tentang Pengadilan Hak Asasi Manusia - Rahadian Diffaul Barraq Suwartono (Universitas Islam Indonesia, 2021)
Pressure from the international community after the disintegration and independence of Timor Leste has prompted the issuance of Law Number 26 of 2000 concerning the Court of Human Rights. However, far from being burnt, the a quo law has received a lot of criticism because it is considered incompatible with its original purpose. This article discusses the fate of regulating war crimes that are not included in the jurisdiction of Law Number 26 of 2000 concerning the Human Rights Court. Through the perspective of legal politics using a conceptual and historical approach, this research answers two problem formulations, first, how is the legal politics of the formation of Law Number 26 of 2000 concerning the Human Rights Court? Second, why does Law Number 26 of 2000 concerning the Human Rights Court not accommodate war crimes? First, it can be concluded that, even though it was born during the reformation period, the a quo law is actually very New Order nuanced. There are inconsistencies in the political will for the formation of the a quo law and its substance. Second, there was the involvement of the TNI and Polri factions in the formulation of Law Number 26 of 2000 concerning the Human Rights Court, which at that time was suspected of being an actor in human rights crimes during the disintegration of Timor Leste after the popular consultation.Keywords: Legal policy; political will; war crimesAbstrakDesakan dari dunia internasional pasca disintegrasi dan kemerdekaan Timor Leste telah mendorong lahirnya Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia. Namun, jauh api dari panggang, undang-undang a quo banyak mendapat kritik karena dianggap tidak sesuai dengan tujuan awalnya. Artikel ini membahas mengenai nasib pengaturan tindak pidana kejahatan perang yang tidak dimasukkan dalam yurisdiksi Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia. Melalui kaca mata politik hukum yang menggunakan pendekatan konseptual dan historis, penelitian ini menjawab dua rumusan masalah, pertama, bagaimana politik hukum pembentukan Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia? Kedua, mengapa Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia tidak mengakomodir tindak pidana kejahatan perang? Dapat disimpulkan pertama, meskipun lahir di masa reformasi, undang-undang a quo justru sangat bernuansa Orde Baru. Terdapat inkonsistensi pada political will pembentukan undang-undang a quo dengan hasil isi substansinya. Kedua, terdapat keterlibatan fraksi TNI dan Polri dalam pembentukan Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia, yang saat itu diduga menjadi aktor kejahatan hak asasi manusia selama masa disintegrasi Timor Leste pasca jajak pendapat.Kata Kunci: Kejahatan perang; politik hukum; political will